The problems of the formation of the pedagogic ideal in the oeuvre by Lesya Ukrainka - Bilan, Tetyana (Actual Problems of Mind, 2017)
The paper considers the essence of the formation of the pedagogic ideal in the oeuvre by Lesya Ukrainka and its preconditions in the traditions of Ukrainian spirituality. The author interrelates the pedagogic paradigm by Lesya Ukrainka with the philosophy of the Ukrainian national idea and considers it actual at the beginning of XXI c.